British travellers’ perspective on the people of the Malay Peninsula in the 19th Century - Inan, Ahmed Cagri; Sivachandralingam Sundara Raja,; Noraini Mohamed Hassan, (Penerbit Universiti Kebangsaan Malaysia, 2024)
Travelogues are narratives that describe events, people, and knowledge in the places visited by the traveller, while also reflecting the traveller’s imagination. Travellers often explore topics outside their comfort zone, such as lifestyle, human relationships, and management styles. Although travelogues were not initially regarded as historical sources, they were later recognised as such. Historians are increasingly interested in travelogues due to the absence of witnesses from the time period mentioned in the narrative, and the significant changes to the architectural and political structure of the region over time. Travelogues can provide a more colourful and subjective perspective on historical studies, augmenting official archive sources with personal accounts. In addition, in these texts, we may encounter different interpretations of events that are not mentioned or deemed unnecessary in official documents. This article will explore travellers’ perspectives of the people of the Malay Peninsula/States in the 19th century with reference to a few renowned British travellers like Isabella Bird, Emily Innes, and Florence Caddy. The perspective that will be explored would be on historical episodes of the time, which is not known in the historical writing of Malaya. The episodes will be highlighted to see how the travellers define the people of Malaya as visitors, what prejudices are contained in their definitions, and how it could contribute to new information on the history of Malaya, is it just based on observation per se or on primary sources accessible at the time? By studying the episodes and the texts, this article would be able to prove that travellers’ writing contributes to enriching Malaysian historical knowledge and is not merely propaganda writing.